2007
DOI: 10.1080/02688690701246210
|View full text |Cite
|
Sign up to set email alerts
|

The use of titanium non-penetrating clips to close the spinal dura

Abstract: We present the results of our initial experience in the use of non-penetrating titanium clips in the closure of spinal dura. A retrospective analysis of case notes of patients identified from the unit database was carried out, limited to adults. A proforma that included demographic details, the diagnosis, the procedure undertaken, whether or not additional dural closure methods were used, the use of bed rest and any complications, including cerebrospinal fluid (CSF) leak. There were 58 patients with a mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 3 publications
0
9
1
Order By: Relevance
“…During the second operation, the dura was noted to have healed completely without adhesions. Unlike Timothy et al , 12 there were no signifi cant complications or CSF leaks in the 1-to 24-month period of follow-up in this study. Six patients required postoperative imaging; however, the clips were found not to interfere with the quality of CT or MRI.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…During the second operation, the dura was noted to have healed completely without adhesions. Unlike Timothy et al , 12 there were no signifi cant complications or CSF leaks in the 1-to 24-month period of follow-up in this study. Six patients required postoperative imaging; however, the clips were found not to interfere with the quality of CT or MRI.…”
Section: Discussioncontrasting
confidence: 76%
“…E538 www.spinejournal.com April 2012 the clips were used for dural closure after excision of intradural lesions, Timothy et al 12 commented on the ease of use, especially in anatomically restricted spaces, and rapid application, but noted an unexpectedly high complication rate. In 8 of their patients, additional methods of dural closure (including suturing with polydioxanone suture, tissue glue ± dural substitute, or muscle patch) were used and approximately half their patients had a period of postoperative bed rest (average of 2.7 days).…”
Section: Discussionmentioning
confidence: 98%
“…It is also unclear how the metal in the U-clip may affect postoperative MRI used for screening for recurrent tumors, for example. Timothy et al 29 reported their experience with nonpenetrating titanium clips for primary dural closure in 58 patients who underwent open (non-MIS) resection for intradural lesions. Eight (13.8%) of the 58 patients developed CSF leakage at an average of 8 days after surgery, which then required additional intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Other adjuncts in the management of durotomies include fibrin glue, muscle patch, dural patch, 8 subfascial drain, 12,15 subarachnoid drain, 29 CT-guided percutaneous fibrin glue patch, 21 and epidural blood patch. We routinely use an intraoperative Valsalva maneuver to check for watertight closure after primary dural repair.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, once the clips are deployed they cannot be repositioned or reused, otherwise there is the risk of dural laceration and graft dislodgment. 36 In this study, it is also possible that the clips were not placed correctly. In fact, there are no data for the number of clips or distance between clips that optimize dural repairs and prevent CSF leaks.…”
Section: Discussionmentioning
confidence: 89%